Catalytic Foldamers: When the Structure Guides the Function - Baptiste Legrand (Catalysts, 2020)
Enzymes are predominantly proteins able to effectively and selectively catalyze highly complex biochemical reactions in mild reaction conditions. Nevertheless, they are limited to the arsenal of reactions that have emerged during natural evolution in compliance with their intrinsic nature, three-dimensional structures and dynamics. They optimally work in physiological conditions for a limited range of reactions, and thus exhibit a low tolerance for solvent and temperature conditions. The de novo design of synthetic highly stable enzymes able to catalyze a broad range of chemical reactions in variable conditions is a great challenge, which requires the development of programmable and finely tunable artificial tools. Interestingly, over the last two decades, chemists developed protein secondary structure mimics to achieve some desirable features of proteins, which are able to interfere with the biological processes. Such non-natural oligomers, so called foldamers, can adopt highly stable and predictable architectures and have extensively demonstrated their attractiveness for widespread applications in fields from biomedical to material science. Foldamer science was more recently considered to provide original solutions to the de novo design of artificial enzymes. This review covers recent developments related to peptidomimetic foldamers with catalytic properties and the principles that have guided their design.